Nature of reactant and influence of water on the supramolecular patterns and luminescent properties of organic salts comprising (1, 1′-biphenyl)-4, 4′-disulfonate and triphenylmethanaminium1. Issue 52 (10th June 2015) - Li, Ya-Nan; Huo, Li-Hua; Deng, Zhao-Peng; Xie, Xin-Yu; Zhu, Zhi-Biao; Gao, Shan
<x xml:space="preserve">Abstract</x> Fourteen supramolecular compounds have been obtained by the reaction of 1, 1′-biphenyl-4, 4′-disulfonic acid and triphenylmethylamine, which exhibit seven types of packing diagram in view of the nature of reactant and influence of water.